Sustainable Packaging Design: Packaging Optimization and Material Reduction for Environmental Protection and Economic Benefits to Industry and Society - Elias D. Georgakoudis; Georgia G. Pechlivanidou; Nicoleta S. Tipi (Applied Sciences)
This paper analyzes the concept of packaging redesign, with the primary objective of improving material utilization. It further examines the potential environmental and economic benefits that may result from effective packaging redesign for both industry and society. The research is based on a specific case study comparing two alternative bottle designs with identical capacity, focusing on shape, material usage, and space efficiency. A detailed numerical comparison highlights the advantages and disadvantages of each option. The analysis demonstrates that an optimized bottle design can lead to substantial material savings and waste reduction. For example, an 8% reduction in bottle weight could eliminate approximately 1.6 million tons of material annually, potentially translating into economic savings exceeding 3 billion U.S. dollars per year. The study underscores how strategic packaging redesign can yield significant benefits in terms of material efficiency and cost savings for companies. It also contributes to the field of Life Cycle Analysis by linking packaging design innovation to key environmental and economic outcomes, while ensuring that packaging continues to protect products and meet the needs of the end consumer.